A transformação de um campo e suas concepções de controle: o caso de uma Santa Casa - Oliveira, Andre Luiz Mendes (Universidade Federal de São Carlos, 2019)
This research investigates a Santa Casa under a relational sociological approach with the aid of Fligstein's Strategic Action Field theory and Conception of Control developed by Fligstein and McAdam. The research theme is presented in order to contextualize the research problem, its objectives and the facts that demonstrate the relevance of the research. The method adopted is the qualitative research, with a unique case study involving documentary research allied to a field research. A brief historical analysis of the Santa Casa is also presented, in order to understand the principles that gave rise to these institutions, and their relationship with Christian charity, philanthropy of the Portuguese nobility and the importance of the Brotherhoods and Confraternities in the Middle Ages in Portuguese societies and Brazilian in the colonial period. A brief history of the Brazilian public health system and of private health plans is outlined. The data were divided in four periods and analyzed considering the four selected categories: Historical Highlights, Provedor Profile, Patient Profile and Financial Resources Source. From this analysis it was possible to identify four conceptions of control over time: Caritária, Nosocômica, Mercantil and Semi-Pública. Another conclusion of the research demonstrates the dynamics of the Santa Casa as a Strategic Action Field, observing the (re) positioning of each of the agents within the Santa Casa field and the fields adjacent to it. The role of the State throughout the history of Santa Casa is also discussed, demonstrating its performance.
The transformation of a field and its conceptions of control: a Santa Casa's case
Keywords: Santas casas; Teoria de campo; Concepções de controle; Campo de ação estratégica; Theory of field; Conception of control; Strategic action field; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE SETORES ESPECIFICOS; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS